Effect of cyclic uniaxial compressive stress on human dental pulp cells in vitro. (4th May 2018) - Yang, Hui; Shu, Yi-Xuan; Wang, Lin-Yan; Zou, Wen-Ling; Guo, Li-Yang; Shao, Mei-Ying; Gao, Qian-Hua; Hu, Tao
ABSTRACT: Purpose : Teeth are exposed to various forces during functional and parafunctional movements. These processes inevitably affect the dental pulp, and the mechanism of these influences has been the subject of many previous studies using different apparatuses and obtaining different results. In this study, we aimed to investigate the effects of compressive stress on the proliferation and differentiation of human dental pulp cells (hDPCs). Materials and Methods : A four-point bending strain system was adopted to apply low-density cyclic uniaxial compressive stress (2000 microstrain, 0.5 Hz) to hDPCs for 1.5, 3, 6, 12, and 24 h. The cell cycle progression and mRNA expression of differentiation-related genes ( BMP2, ALP, DMP1, DSPP, COL I ) were then examined to investigate the proliferation and differentiation of hDPCs. Results : The results showed that cyclic compressive stress changed the morphology of hDPCs after 12 and 24 h of mechanical loading; cell cycle progression was promoted, especially in the 24-h group ( p < 0.05). The expression of BMP2 was significantly upregulated after 3 and 6 h of mechanical loading but declined in the 12- and 24-h groups, whereas the expression levels of DMP1 and DSPP were significantly upregulated in the 12- and 24-h loading groups ( p < 0.05). Conclusions : Dental pulp cells were sensitive to compressive stress, especially after 12 and 24 h of applied force. Proliferation and odontogenic differentiation were significantly promoted in this in vitro model.